THE INFLUENCE OF TAMANSISWA’S TEACHINGS TRI PANTANGAN, ATTITUDES, AND GIVING REWARDS ON THE INTENTION TO CARRY OUT WHISTLEBLOWING - Wardani, Dewi Kusuma; Agustina, Rini (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Whistleblowing is an action taken by someone to reveal an act of fraud. Whistleblowing can be improved by various factors such as the teachings of “tri pantangan”, attitude and giving rewards. The purpose of this research is to analyze the influence of the teachings of “tri pantangan”, attitudes, and giving rewards. This research uses a quantitative approach with a sample of 100 respondents as primary data, using SPSS version 20. The findings in this research show that the teachings of “tri pantangan” have a positive effect on the intention to whistleblowing, attitudes have no effect on the intention to whistleblowing, and giving rewards has a negative effect regarding intentions to carry out whistleblowing.